A "Era Lula" e suas interpretações no interior do Serviço Social - Santana, Bruna da Paixão (2018)
The present investigation has as object of study the interpretations of the government of Luiz Inácio Lula da Silva (2003-2010) within the Social Work. In considering the concrete expressions of the dynamicity of social life in this period, which produce and reproduce significant refutations for the working class, including for the professional practice of social workers, it has become imperative to analyze which interpretative tendencies predominate in the bibliographic productions within the profession, which conformed as the general objective of the present study. To achieve this, we debate the particularities of the constitution of capitalism in the country, focusing on the relations established between the State and civil society that shape the processes of disputes over hegemony. We also approach the main debates about the model of regulation and the strategies of hegemony that attempt to characterize the Lula government, considering the analytical clash between neo-liberal and neo-descendant theses. From the analysis of the publications made by intellectuals of our professional category in the magazine Serviço Social & Sociedade, we find three analytical tendencies regarding the period on screen which shows that there is also no consensus about this debate in Social Work. The perspective that supports the deepening of neoliberal hegemony and that opposes the idea that the neo-descendant principles materialized (whether wholly or partially) proved to be the most predominant of the articles analyzed.